2008
DOI: 10.2217/17435889.3.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Biodegradable Nanofibrous Mats for Tissue Engineering

Abstract: All scaffolds prepared by electrospinning have implied significant potential for use in further studies leading to bone tissue engineering applications. The PHBV-PLLA blend appeared to yield the best results regarding cell number increase, their attachment and spreading inside and on the scaffold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 47 publications
0
42
0
Order By: Relevance
“…The PHBV is a material with suitable properties for cellular growth and adhesion with controllable degradation (Meng et al, 2007;Dreu et al, 2008;Li & Xia, 2004). Nanofi bers have improved the performance of biomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…The PHBV is a material with suitable properties for cellular growth and adhesion with controllable degradation (Meng et al, 2007;Dreu et al, 2008;Li & Xia, 2004). Nanofi bers have improved the performance of biomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…We have also observed the effect of this salt on e-spun PHBV-8 fiber morphology. 82 PHBV-8 fiber structure that was produced from solutions containing no salt had resulted in bead formation and fibers were not straight. When salt was added, bead formation was prevented and more straight fibers were obtained 82 86 (Fig.…”
mentioning
confidence: 99%
“…The relative fiber diameters of the blended polymers were ranked as following: PLA > PLA/PCL (7/3) > PLA/PCL (5/5) > PLA/PCL (3/7) > PCL. Many studies have reported that fibrous membranes blended with different biodegradable polymers by an electrospinning technique resulted in a range of diameter distributions from 10 nm to a few micrometer [11,12].…”
Section: Discussionmentioning
confidence: 99%